Documentation of German real estate market data: Sample of real estate advertisements on the internet platform ImmobilienScout24, 2007-2013 - Philipp an de Meulen; Martin Micheli; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This data report presents a dataset on residential real estate prices in Germany provided by ImmobilienScout24 and introduces real estate price indices of labor market regions. The dataset consists of online adverts of houses and apartments that are available for rent or sale. The dataset complements already existing datasets in two ways: First, it is available almost without any time lag, allowing the analysis of most recent developments. Second, the high market share of ImmobilienScout24 results in a high number of observations, which gives the opportunity to use the data for analyses on a small regional scale.
Keywords: 330